Environment and poverty : key linkages for global sustainable development - Rahman, A. Atiq.; Hurtado, Maria Elena; International Workshop on Environment and Poverty (1993 : Dhaka, Bangladesh) (Dhaka : University Press, 1998)
Contributed papers presented at the International Workshop on Environment and Poverty held at Dhaka, Bangladesh in July 1993.
Keywords: Environmental policy -- Bangladesh -- Congresses; Sustainable development -- Bangladesh -- Congresses; Economic development -- Environmental aspects -- Bangladesh -- Congresses; Poverty -- Bangladesh